"Graeca non leguntur?" zu den Ursprüngen des europäischen Rechts im antiken Griechenland - Barta, Heinz (Harrassowitz Verlag, 2010)
The four volumes of 'Graeca non leguntur'? are the result of many years of research on the Greeks and their legal-historical environment. It is about the important question of whether the widespread opinion is correct that the legal foundations of Europe are to be regarded exclusively as achievements of Rome. - This impression is erroneously given by scientists. Because it can be proven that some of what was previously considered Roman came from ancient Greece. The ancient Orient often hides behind the Greek origin. The emergence of European jurisprudence in ancient Greece is dealt with in ten chapters: Volume I (Introduction + Chapter I: Historical Perspectives); Volume II (Drakon and Solon as legislators and legal thinkers); Volume III deals with the networked Greek culture as a whole and deals with the areas of poetry (Aeschylus and Euripides) and historiography (Thukydides) that are important for Greek legal thought, including the early legal professionalization; Volume IV deals with the thinkers Plato, Aristotle and Theophrastus, who were important for the development of law. Chapter IX deals with law, religion and justice in early societies. Chapter X ventures an outlook on the present and future. Chapter XI summarizes.